2021
DOI: 10.1128/iai.00451-20
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Mechanistic Correlates of Protection Conferred by Whole-Cell Vaccination against Pseudomonas aeruginosa Acute Murine Pneumonia

Abstract: Pseudomonas aeruginosa is a Gram-negative pathogen that causes severe pulmonary infections associated with high morbidity and mortality in immunocompromised patients. The development of a vaccine against P. aeruginosa could help prevent infections caused by this highly antibiotic-resistant microorganism. We propose that identifying the vaccine-induced correlates of protection against P. aeruginosa will facilitate the development of a vaccine against this pathogen. In this study, we studied the mechanistic corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…S8). Together, the trends from these data showed the importance of neutrophil recruitment in the response against P. aeruginosa infection (30,47,48).…”
Section: Neutrophils Mediate the Clearance Of P Aeruginosa From Vacci...mentioning
confidence: 75%
See 1 more Smart Citation
“…S8). Together, the trends from these data showed the importance of neutrophil recruitment in the response against P. aeruginosa infection (30,47,48).…”
Section: Neutrophils Mediate the Clearance Of P Aeruginosa From Vacci...mentioning
confidence: 75%
“…Treatment options for multidrug-resistant P. aeruginosa are limited (28,29). Many experimental vaccines have demonstrated potential, but none have been clinically approved (30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive production of TNF-α or other proinflammatory cytokines in the lungs of PBS-, rOMV-N-, or PH-immunized animals will result in immune dysregulation, leading to ineffectively clearing bacteria, loss of lung function, and eventually death. Intriguingly, Sen-Kilic et al recently highlighted the importance of the humoral immune response for protection against P. aeruginosa infection and showed that passive immunization with serum from mice vaccinated with a curdlan-adjuvanted P. aeruginosa whole-cell vaccine (WCV) alone protected naive mice against P. aeruginosa ( 64 ). However, our results in antibody passive immunization and T-cell depletion were inconsistent with their observations.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme linked immunosorbent assay (ELISA) was utilized to measure antigen-specific antibodies in the serum of immunized mice (52)(53)(54). After euthanasia, blood was collected in BD Microtainer serum separator tubes (BD, Cat.…”
Section: Serological Analysis Of Immunized Micementioning
confidence: 99%